2014
DOI: 10.1002/acn3.117
|View full text |Cite
|
Sign up to set email alerts
|

Smads as muscle biomarkers in amyotrophic lateral sclerosis

Abstract: ObjectiveTo identify molecular signatures in muscle from patients with amyotrophic lateral sclerosis (ALS) that could provide insight into the disease process and serve as biomarkers.MethodsRNA sequencing was performed on ALS and control muscle samples to identify Smad family members as potential markers of disease. Validation studies were performed in a cohort of 27 ALS patients and 33 controls. The markers were assessed in the G93A superoxide dismutase (SOD)1 mouse at different stages of disease and in a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(77 citation statements)
references
References 46 publications
11
66
0
Order By: Relevance
“…Non-transgenic littermates were used as controls. For the G93A SOD1 mice, clinical progression was evaluated by weight determination and performance on the rotarod as described previously [ 4 ]. End stage disease was determined when the mouse could not right itself after 30 seconds when placed on its side.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-transgenic littermates were used as controls. For the G93A SOD1 mice, clinical progression was evaluated by weight determination and performance on the rotarod as described previously [ 4 ]. End stage disease was determined when the mouse could not right itself after 30 seconds when placed on its side.…”
Section: Methodsmentioning
confidence: 99%
“…In the ALS mouse, pathological changes can first be detected in muscle and the neuromuscular junction prior to motor neuron loss, indicating that these structures can reflect early disease activity [ 1 3 ]. We recently identified members of the Smad family (Smads1, 5, and 8) as muscle biomarkers of disease progression in ALS [ 4 ]. These Smads are upregulated and activated in the ALS mouse at an early stage, before overt clinical signs are present, suggesting they may also be markers of disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…The down regulation of SCD1 (Stearoyl-CoA desaturase 1) in the muscle of ALS patients also confirmed the relevant role of muscle in pathogenesis [87]. Recent studies described the involvement of muscle in the motor neuron degeneresence mechanisms through: the UCP1 (uncoupling protein 1) protein [88], SOD1 [89], neurotrophin 4, BMP (Bone morphogenetic) proteins, Smads [55,[90][91][92], Akt and Factor XIIIB [93]. Elf et al [94] recently performed a shotgun proteomics and quantitative dimethyl labeling to evaluate the human skeletal muscle proteome of ALS and reported a panel of 11 proteins.…”
Section: Muscle Proteins To Explore Pathophysiologymentioning
confidence: 67%
“…Potentially more sensitive thematic transcriptomic approaches focused on pathophysiological mechanisms can also be used. Several RNA expressed in non-neural tissues, such as Smad RNA in muscle, have been proposed as potential ALS biomarkers [55][56]. Studies on the expression of miRNAs found in biological fluids that are considered to be stable, such as CSF, blood and urine could also provide biomarkers in ALS [57][58] through global method i.e.…”
Section: Transcriptsmentioning
confidence: 99%
“…Muscle transcriptome analyses have found that smad1, 5, 8 mRNA and protein levels, as well as Smad phosphorylation, were elevated in ALS muscle. Therefore, muscle smads could serve as potential candidates for ALS biomarkers [ 47 ].…”
Section: Introductionmentioning
confidence: 99%